Performance of parametric transducer arrays and its relationship with the carrier frequency - Xiao, Jingxuan (Nanyang Technological University, 2022)
Personal privacy is an imperative consideration, and this extends to listening privately via the ear speaker, earphone or headphones of electronic acoustical devices.